DETERMINANTS OF UNDERWRITING FEES FOR DOMESTIC AND NON-DOMESTIC SEASONED EQUITY OFFERINGS BY CANADIAN CROSS-LISTED SHARES - Kryzanowski, Lawrence; Rubalcava, Arturo (Assurances, 2002)
This paper examines whether the determinants of underwriter fees are the same for domestic and non-domestic seasoned equity offerings (SEOs) by Canadian shares cross-listed on the TSE and on the NYSE/AMEX and NASDAQ. The results indicate that gross proceeds, firm size, return volatility, relative size of the offering and the inclusion of an overallotment option are the determinants of fees for domestic SEOs. Firm size, number of underwriters, type of offering and U.S. listing venue are the determinants of underwriting fees for non-domestic SEOs. After controlling for differences in other relevant fee determinants, underwriter fees are significantly higher for non-domestic compared to domestic SEOs, and for non-domestic SEOs for Canadian shares cross-listed on the NASDAQ compared to those cross-listed on the NYSE/AMEX. These results suggest that the Canadian and the U.S. investment banking markets are not integrated in the sense of sharing underwriting cost functions with an identical set of determinants.